2014
DOI: 10.1007/s00436-013-3746-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of spermatozoa in the seminal receptacle of the liver fluke Opisthorchis felineus (Rivolta, 1884)

Abstract: The spermatozoon ultrastructure in the seminal receptacle of the liver fluke Opisthorchis felineus (Digenea, Opisthorchiidae), the agent of human opisthorchiasis endemic to Russia and Eastern Europe, was examined. The bean-shaped seminal receptacle of O. felineus has a wall consisting of epithelial and muscle layers. Mature spermatozoa are located in the interior of the seminal receptacle, whereas vacuoles containing degenerating spermatozoa are detectable at the periphery. The mature spermatozoon of O. feline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…The mature spermatozoon of N. aspidogastriformis presents two mitochondria with a first one in the ornamented area, and a second one more posteriorly located, i.e., in the nuclear region. Similar disposition of mitochondria had been reported in other digeneans such as the opecoelids Poracanthium furcatum, Nicolla testiobliquum, and N. wisniewskii (Levron et al, 2004b;Quilichini et al, 2007b, c), the dicrocoeliid Dicrocoelium hospes (Agostini et al, 2005), the troglotrematid Troglotrema acutum (Miquel et al, 2006), the omphalometrid Rubenstrema exasperatum (Bakhoum et al, 2011), or the opisthorchiid Opisthorchis felineus (Zhukova et al, 2014). Within the Lepocreadioidea, two mitochondria have been described in R. fractum, H. caputvadum, and O. bacillaris Kacem et al, 2012;Ndiaye et al, 2015), whereas in the remaining species only one mitochondrion has been reported Quilichini et al, 2011b).…”
Section: Number Of Mitochondriasupporting
confidence: 73%
See 2 more Smart Citations
“…The mature spermatozoon of N. aspidogastriformis presents two mitochondria with a first one in the ornamented area, and a second one more posteriorly located, i.e., in the nuclear region. Similar disposition of mitochondria had been reported in other digeneans such as the opecoelids Poracanthium furcatum, Nicolla testiobliquum, and N. wisniewskii (Levron et al, 2004b;Quilichini et al, 2007b, c), the dicrocoeliid Dicrocoelium hospes (Agostini et al, 2005), the troglotrematid Troglotrema acutum (Miquel et al, 2006), the omphalometrid Rubenstrema exasperatum (Bakhoum et al, 2011), or the opisthorchiid Opisthorchis felineus (Zhukova et al, 2014). Within the Lepocreadioidea, two mitochondria have been described in R. fractum, H. caputvadum, and O. bacillaris Kacem et al, 2012;Ndiaye et al, 2015), whereas in the remaining species only one mitochondrion has been reported Quilichini et al, 2011b).…”
Section: Number Of Mitochondriasupporting
confidence: 73%
“…The anterior spermatozoon extremity of N. aspidogastriformis forms a sharp point. This is the most frequent morphology described in digenean species (Ndiaye et al, ; Agostini et al, ; Quilichini et al, ; Bakhoum et al, ; Zhukova et al, ). In cross‐section, the anterior extremity of the mature spermatozoon of N. aspidogastriformis exhibits one axoneme associated with antero‐lateral electron‐dense material.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, these ultrastructural criteria possess great phylogenetic interest in understanding the complexes relationships within Digenea in general and Dicrocoeliidae in particular (Agostini et al, 2005;Bakhoum et al, 2013a;Miquel et al, 2013;Quilichini et al, 2010b;Ternengo et al, 2009;Zhukova et al, 2014). Five ultrastructural characteristics present in the spermatozoon of B. eliomydis, are discussed below.…”
Section: Characters Of Phylogenetic Interestsmentioning
confidence: 99%
“…In all monorchiid species described so far the posterior spermatozoon extremity contains a nucleus as in O. dinema and P. selaris (Table 1). This morphology of the posterior spermatozoon extremity is frequently reported in digenean (Kacem et al, 2010(Kacem et al, , 2015aZhukova, Mordvinov & Kiseleva, 2014;Quilichini et al, 2015) and corresponds to the fasciolidean type or type 2 according to the diagram of Quilichini et al…”
Section: -Posterior Spermatozoon Charactersmentioning
confidence: 52%